EFEKTIVITAS PROMOSI KESEHATAN DENGAN MEDIA YOUTUBE DAN QUIZIZZ TERHADAP PENGETAHUAN REMAJA TENTANG DAMPAK PENGGUNAAN GAME ONLINE PADA KELAS VII SMPN 16 BEKASI - Putri Lestari (2022)
The high number of online game users in teenagers is influenced by the low knowledge of teenagers about the impact of using online games. The survey results of the Indonesian Internet Service Providers Association (2020) noted that one of the entertainment content that was chosen by many Indonesians was online games at 16,5%. Online games have a negative impact, especially on teenagers development. Providing health promotion by utilizing YouTube and Quizizz as information media to increase knowledge, especially forteenagers. The purpose of this study was to determine the effectiveness of health promotion with YouTube and Quizizz on teenagers knowledge about the impact of using online games. This study uses a quasi-experimental design with a pretest and posttest two group design. This research was conducted on June 15, 2022 with a sample of 78 students obtained using a non-probability sampling technique with purposive sampling. The population in this study were 210 seventh grade students. Statistical test using paired t-test and independent t-test. Based on the data collected, it was found that the average value of teenagers knowledge after health promotion in the youtube group was 89,13 not much different from the quizizz group 89,82. The use of youtube and quizizz media is effectively used as a media for health promotion on teenagers knowledge about the impact of using online games. It is hoped that YouTube and Quizizz media can be used as references for health workers in providing health promotion to teenagers.